2022
DOI: 10.1186/s12889-022-14214-5
|View full text |Cite
|
Sign up to set email alerts
|

Flight crew fatigue risk assessment for international flights under the COVID-19 outbreak response exemption policy

Abstract: Background In response to the COVID-19 outbreak, the Civil Aviation Administration of China (CAAC) has formulated Implementation Measures for Exemption of Crew Duty Periods and Flight Time Restrictions during the COVID-19 Outbreak. This exemption policy imposes temporary deviations from the approved crew duty periods and flight time restrictions for some transport airlines and regulates the use of multiple crews for continuous round-trip flights. However, no research has been conducted on fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…After each set of tasks had been completed, we allowed the subjects to rest for 5 min and complete the 9-point Karolinska Sleepiness Scale during this rest period to assess their fatigue status as a score from 1 to 9 [31]. The result was used to categorize the controller's fatigue status as no fatigue, mild fatigue, or severe fatigue [32]. At the beginning of the experiment, the scale assessment results showed that the subjects were mostly in a no-fatigue state.…”
Section: Methodsmentioning
confidence: 99%
“…After each set of tasks had been completed, we allowed the subjects to rest for 5 min and complete the 9-point Karolinska Sleepiness Scale during this rest period to assess their fatigue status as a score from 1 to 9 [31]. The result was used to categorize the controller's fatigue status as no fatigue, mild fatigue, or severe fatigue [32]. At the beginning of the experiment, the scale assessment results showed that the subjects were mostly in a no-fatigue state.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional approach to fatigue risk management is to specify fixed Flight and Duty Time Limitations (FTL) for duty and rest periods, but around 2010, international civil aviation began to pursue a performance-based approach to safety management in the area of fatigue, namely the Fatigue Risk Management System (FRMS). Management System (FRMS) [1] , and the research and application of FRMS reached a new climax during the COVID-19 epidemic due to the special requirements such as crew isolation and the creation of licensed operation methods that deviate from FTL [2,3,4] .…”
Section: Introductionmentioning
confidence: 99%